Madhav Sadashivrao Golwalkar And His Thoughts On Social Harmony - TAMTA, DR. SEEMA (The journal of contemporary issues in business and government, 2021)
India has been a hub of many well-known political thinkers who have contributed immensely to different realms of Social Sciences. India has had a diverse array of thinkers, from Swami Vivekananda to Mahatma Gandhi, Dr B.R. Ambedkar, Pt Deen Dayal Upadhyay and many more, who have not only presented their views on several political-social-economic problems and situations, but also tried to present effective solutions for the same through their respective ideologies. The ideas and views of these personalities still serve as a guide and help in devising roadmaps to the future not only for India but for the entire international community. The ideologies of these great men have not only been useful and relevant in their time period, but they are thinkers still seem to be relevant in the modern era as they were during that period. The philosophy of these personalities have provided solutions to many problems and issues of the society, also gave rise to many significant changes in the social, political, and cultural areas that the world has witnessed. Thinkers and social reformers like Jyotiba Phule, Periyar, Dr. B. R. Ambedkar, Mahatma Gandhi and Madhav Sadashivrao Golwalkar have indeed left an indelible mark on the Indian people and social structure.